Interações entre mães e suas crianças deficientes: uma proposta de análise segundo a teoria da intersubjetividade inata - Vedovato, Aline Giovanne (2007)
This study aimed to understand how interactions between mothers and their disabled children take place, based upon the theory of Innate Intersubjectivity, as well as to investigate main difficulties they faced in their daily activities. Four mothers and their children (aged between 1 to 2 years old) with some sort of disability participated in this research. Data were collected through video recordings in three different situations: feeding, bathing, and playing, in the participants homes. Videos were analyzed frame-by-frame and results showed that hindrances in interactions may cause difficulties in the child s physical and emotional development, as well as influencing the origin of psychofunctional and psychopathological symptoms in mothers and children. It s expected that this research may contribute to the increase of knowledge about the topic, motivating other professionals and researchers to its extension.